Leptospirosis Associated Digital Gangrene of Lower Extremities: Two Cases and Review of Literature - Dinkar, Anju; Singh, Jitendra; Yadav, Mahima (Infectious Disorders - Drug Targets, 2024)
Background: Leptospirosis is the most common zoonotic illness worldwide, caused by pathogenic spirochete bacteria called Leptospirosis. It is clinically presented with mild to moderate in most cases. However, sometimes, the course may be severe with multiorgan dysfunction. Case Presentation: We present two rare cases of Leptospirosis with peripheral dry gangrene of the lower extremities. A 25-year-old male, farmer by occupation without any significant past medical history had been diagnosed with a case of Leptospirosis that complicated to digital gangrene on 15 days of illness during hospitalization. Another 21-year-old male student was admitted for leptospirosis and developed digital gangrene on 19 days of illness. All clinical findings were resolved on the steroid. Conclusion: Apart from a high index of suspicion and awareness of unusual manifestations, serology plays a vital role in making an accurate and quick diagnosis to initiate appropriate therapy.
Keywords: vasculitis